Application of a healthy food markets guide to two Indonesian markets to reduce transmission of “avian flu” - Samaan, Gina (World Health Organization, 2012)
PROBLEM: The World Health Organization (WHO) developed a guideline with 10 control measures to reduce transmission of A(H5N1) avian influenza virus in markets in low-resource settings. The practical aspects of guide implementation have never been described. APPROACH: WHO’s guideline was implemented in two Indonesian markets in the city of Makassar to try to reduce transmission of the A(H5N1) virus. The guideline was operationalized using a participatory approach to introduce a combination of infrastructural and behavioural changes. LOCAL SETTING: Avian influenza is endemic in birds in Makassar. Two of the city’s 22 dilapidated, poorly-run bird markets were chosen for the study. Before the intervention, neither market was following any of WHO’s 10 recommended control measures except for batch processing. RELEVANT CHANGES: Market stakeholders’ knowledge about the avian influenza A(H5N1) virus improved after the interventions. WHO guideline recommendations for visual inspection, cleaning and poultry-holding practices, as well as infrastructural requirements for zoning and for water supply and utilities, began to conform to the WHO guideline. Low-maintenance solutions such as installation of wastewater treatment systems and economic incentives such as composting were well received and appropriate for the low-resource setting. LESSONS LEARNT: Combining infrastructural changes with behaviour change interventions was critical to guideline implementation. Despite initial resistance to behaviour change, the participatory approach involving monthly consultations and educational sessions facilitated the adoption of safe food-handling practices and sanitation. Market authorities assumed important leadership roles during the interventions and this helped shift attitudes towards regulation and market maintenance needs. This shift may enhance the sustainability of the interventions.